1990
DOI: 10.1046/j.1537-2995.1990.30891020332.x
|View full text |Cite
|
Sign up to set email alerts
|

In vivo viability and functional integrity of filtered platelets

Abstract: The in vivo viability and functional integrity of filtered platelets were compared with those of nonfiltered platelets in a controlled study. On two occasions, after template bleeding time, 14 healthy volunteers underwent plateletpheresis and received 600 mg of aspirin. Autologous 111In-labeled platelets were transfused without further manipulation (control) on one occasion and after filtration on a second occasion. The filter was primed and flushed with a buffered 12.6-percent solution of ACD-A in 0.9-percent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
4
1

Year Published

1993
1993
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 21 publications
2
4
1
Order By: Relevance
“…Some investigators have questioned the rationale of comparing the ability of platelets to correct an aspirin‐induced thrombocytopathy in normal volunteers with platelet function in the treatment of thrombocytopenic patients 31,32 . Results from our previous studies in human volunteers 8‐10 and from this study in the baboon are similar to those reported by Khuri et al 7 when cardiopulmonary bypass patients received transfusion of allogeneic liquid‐preserved platelets stored for a mean of 3.4 days and allogeneic previously frozen washed platelets.…”
Section: Discussionsupporting
confidence: 79%
“…Some investigators have questioned the rationale of comparing the ability of platelets to correct an aspirin‐induced thrombocytopathy in normal volunteers with platelet function in the treatment of thrombocytopenic patients 31,32 . Results from our previous studies in human volunteers 8‐10 and from this study in the baboon are similar to those reported by Khuri et al 7 when cardiopulmonary bypass patients received transfusion of allogeneic liquid‐preserved platelets stored for a mean of 3.4 days and allogeneic previously frozen washed platelets.…”
Section: Discussionsupporting
confidence: 79%
“…Contrary to that assumption, our studies of autologous fresh, liquid‐preserved, or cryopreserved PLTs in aspirin‐treated baboons showed no correlation between the survival of the preserved non–aspirin‐treated PLTs and their function to reduce the prolonged BT and increase the thromboxane level in the shed blood 167 . Pineda and associates 200 and Brecher and associates 201 have compared the survival and function of various PLT products in human aspirin‐treated volunteers. They studied autologous non–aspirin‐treated washed and nonwashed PLTs and filtered PLTs and nonfiltered PLTs.…”
Section: Quality Of Fresh and Preserved Pltscontrasting
confidence: 76%
“…Findings from a prospective randomized study in CPB surgery patients comparing the survival and function of washed previously frozen PLTs to values for liquid‐preserved PLTs indicated that results were similar to those observed when washed previously frozen PLTs and liquid‐preserved PLTs were transfused to aspirin‐treated human volunteers and baboons 162‐168,184 . We suggest that this lends credence to studies comparing the survival and function of autologous preserved PLTs in aspirin‐treated human volunteers 162‐166,200,201 …”
Section: Quality Of Fresh and Preserved Pltssupporting
confidence: 54%
See 1 more Smart Citation
“…In our studies of autologous fresh, liquid‐preserved, or cryopreserved PLTs in aspirin‐treated baboons, we observed no correlation between the survival of the preserved non–aspirin‐treated PLTs and their function to reduce the prolonged bleeding time and increase the thromboxane level in the shed blood 6 . Pineda and associates 8 and Brecher and associates 9 have compared the survival and function of autologous non–aspirin‐treated washed and nonwashed PLTs and of filtered PLTs and nonfiltered PLTs in aspirin‐treated human volunteers. Investigators have questioned the relevance of the studies of the survival and function of non–aspirin‐treated preserved PLTs in aspirin‐treated human volunteers and aspirin‐treated baboons to the survival and function of preserved PLTs to treat anemic and thrombocytopenic patients 7 .…”
mentioning
confidence: 72%